"There Is Method to This Madness" A Qualitative Investigation of Home Medication Management by Older Adults - Olajide Fadare; Matthew Witry (MDPI AG, 2023)
Objectives: This paper explores (1) the systems and processes older adults use to manage medications at home, and (2) the well-being goals of personal interest that motivate them. Methods: Qualitative interviews were conducted in the homes of 12 older adults in a small city in the Midwest United States. Interviews were analyzed using inductive template analysis. Results: The average age of older adults in this study was 74.2 years (SD = 10.5), 66.7% were women. The most prominent home medication management tools used were pill boxes, containers and vials, and medication lists. Routines were often aligned with activities of daily living such as teeth brushing and eating. Their medication management work occurred in contexts of other household members and budget constraints. Routines and practices were sometimes idiosyncratic adaptations and supported goals of maintaining control and decreasing vulnerability. Conclusion: In developing routines for home medication management, older adults developed systems and deliberate processes to make sense of their medication experiences in the context of their home environment and based on available resources.